2001
DOI: 10.1139/cjfas-58-9-1891
|View full text |Cite
|
Sign up to set email alerts
|

Surplus production, variability, and climate change in the great sardine and anchovy fisheries

Abstract: We used fishery and survey data to calculate annual surplus production (ASP) and instantaneous surplus production rates (ISPR) for eight anchovy and nine sardine stocks. In addition, we calculated ASP per unit spawning area for six anchovy and six sardine stocks. Median ASP was highest for stocks with highest median biomass (mostly anchovies), and ASP was typically about 16% of stock biomass. ASP was often negative, more frequently for anchovies (36% of years) than for sardines (17% of years). ISPR was less va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 16 publications
2
30
0
1
Order By: Relevance
“…Climate‐sensitive upwellings of nutrient‐rich waters support huge catches of anchovies and sardines, primarily off Peru and Chile (Pauly and Tsukayama 1987; Bakun and Broad 2003). Catches of small pelagic fishes have been as high as 11 million tonnes per year, more than 10% of world capture fish production (FAO 2004), but show pronounced fluctuations in relation to changes in the El Niño Southern Oscillation (Jacobson et al. 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Climate‐sensitive upwellings of nutrient‐rich waters support huge catches of anchovies and sardines, primarily off Peru and Chile (Pauly and Tsukayama 1987; Bakun and Broad 2003). Catches of small pelagic fishes have been as high as 11 million tonnes per year, more than 10% of world capture fish production (FAO 2004), but show pronounced fluctuations in relation to changes in the El Niño Southern Oscillation (Jacobson et al. 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Mature biomass tracks the population's resilience, as accumulated biomass from adults can sustain populations through times of scarcity (Warner & Chesson, ). Annual population production provides a good proxy for short‐term productivity (Denney, Jennings, & Reynolds, ) and has been proposed as a metric for detecting environmentally induced variation (Jacobson et al., ). Our goal throughout was to characterize, as realistically and faithfully as possible, the type of variability in recruitment and somatic growth as well as underlying population structure and demographic rates of each species.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies indicated that the climate anomalies might have potential impacts on the dispersal of long‐distance migratory fishes (Chang, Sheng, Ohashi, Béguer‐Pon, & Miyazawa, ; Han et al, ; Jacobson et al, ). Based on the above analysis, an autocorrelation analysis was performed for the time series analysis of the year effect coefficient to explore the factors influencing the population trend of whitespotted conger during 2011–2017.…”
Section: Methodsmentioning
confidence: 99%